Effect of postbiotic-toothpaste on salivary levels of IgA in 6- to 12-year-old children: Study protocol for a randomized triple-blind placebo-controlled trial - Basir, Leila; Moghimipour, Eskandar; Saadatzadeh, Afrooz; Cheraghian, Bahman; Khanehmasjedi, Samaneh (Frontiers in Pediatrics, 2022)
Background: Children in mixed dentition are highly at risk for dental caries, which is a major health issue worldwide. Despite their effect in controlling dental caries, using probiotics can be challenging. Therefore, it has been advised to use their inanimate forms, called postbiotics. We hypothesize that postbiotics can enhance the oral immunity. Methods: The aim of this triple-blind, randomized, placebo-controlled trial is to investigate the effect of postbiotic-toothpaste (Bifidobacterium animalis subsp. animalis) on salivary levels of Immunoglobulin A (IgA) and pH in children. Using comparing two means formula to calculate the sample size, for this trial 80 healthy 6- to 12-year-old children during mixed dentition with no cavitated dental caries will be selected by convenience sampling method and randomly allocated to two groups, postbiotic-toothpaste or placebo-toothpaste. Saliva samples will be gathered at baseline and four weeks after the intervention. The level of salivary IgA will be determined by ELISA and salivary pH will be measured using a pH meter. Data will be compared within and between groups using independent t-test and paired t-test, in case of normality, with a p<0.05 as statistically significant. Discussion: If postbiotics-toothpaste prove to be effective in improving the oral immunity, they can be used to prevent dental caries and other oral diseases. The result of this study can help researchers who are working on the immunomodulatory effects of postbiotics in children. Trial registration number: Iranian Registry of Clinical Trials (IRCT), IRCT20191016045128N2. Registered on 7 March 2022